Why Not Their Way? - Ani Purjayanti (Universitas Muhammadiyah Semarang, 2017)
The way information is disseminated and learned is changing rapidly. What used to be meaningful sources of information in the past may be less preferred these days. As this trend has been touching nearly all aspects of life, it also brings about vast impacts in the teaching and learning process. Moreover, we are now dealing with the Y generation which obviously has distinct characteristics compared to the previous ones. Unfortunately, in the university where I teach, the way the material presented remains unchanged: a workbook prepared by the academic commitee for 29 diverse study programs. This paper, hereby, aims to explore a variety of ways in which this book can still be utilized but taking students’ learning preference into accountall at once. Needs analysis containing students’ learning preference were then distributed at the end of the first meeting, followed by a small discussion for better clarification. Then it is analyzed and clustered in order to obtain a clear picture on how the material available can be developed into a meaningful interesting source. Several activities and additional materials were next designed to cater for students’ dynamic participation in exploring the workbook. Students were asked to express their impression on material discussed after each meeting, and this was then discussed in week 7. It is revealed that with activities they like, classroom materials can be turned into something interesting.